Realism and presence in simulation: Nursing student perceptions and learning outcomes - Maclean, Sharon; Geddes, F.; Kelly, Michelle; Della, Phill (SLACK INC, 2019)
Background: Research examining how perceived realism and presence affects participants’ learning experiences and outcomes is limited.